Metabolit Bioaktif Bakteri: Tinjauan tentang Potensi Antimikroba dan Aplikasinya - Nova, Bastian; Supri Wardi, Epi; Sartika, Diza (Journal of Pharmaceutical and Sciences, 2024)
Bacteria are a promising source of bioactive compounds. This review provides a concise overview of existing research on antimicrobial molecules from bacteria. Additionally, it briefly summarizes bacteriocins, non-ribosomal peptides, polyketides, and lipopeptides targeting pathogens resistant to several drugs, considering next-generation antibiotics. The review highlights the potential use of bacteria as a source of antimicrobials for biotechnological, nutraceutical, and pharmaceutical applications. However, further investigation is needed to isolate, separate, purify, and characterize these bioactive compounds, as well as to formulate them into clinically approved antibiotics.